2021
DOI: 10.1080/1359432x.2021.1952990
|View full text |Cite
|
Sign up to set email alerts
|

Using strengths and thriving at work: The role of colleague strengths recognition and organizational context

Abstract: According to the socially embedded model of thriving at work, employees thrive (i.e., experience a sense of vitality and learning), when they can engage in agentic work behaviours. In this study, we first examine whether strengths use can be seen as an agentic work behaviour that contributes to thriving. Second, we investigate whether the degree to which colleagues recognize each other's strengths boosts the positive relationship between strengths use and thriving. Third, we propose that perceived organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Future research should attempt to consider the affective mechanism through which growth mindset positively relates to innovative behavior. Third, according to the extant literature on strength-based approaches, strengths-based psychological climate and organizational support for strengths use similar to strengths-based leadership can also send an important signal to employees that employee strengths use is appreciated and encouraged by the organization (Van Woerkom et al, 2020 ; Moore et al, 2021 ). Future research should investigate whether other types of strengths-based approaches can also strengthen these relationships between growth mindset, strengths use, and innovative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should attempt to consider the affective mechanism through which growth mindset positively relates to innovative behavior. Third, according to the extant literature on strength-based approaches, strengths-based psychological climate and organizational support for strengths use similar to strengths-based leadership can also send an important signal to employees that employee strengths use is appreciated and encouraged by the organization (Van Woerkom et al, 2020 ; Moore et al, 2021 ). Future research should investigate whether other types of strengths-based approaches can also strengthen these relationships between growth mindset, strengths use, and innovative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…96 The ability to see the strengths in someone's work and personality, and use these strengths as complements to one own's. 96 However, more research is needed into how this could be done effectively in ICU teams. A final factor that we would like to discuss in effective team building is leadership.…”
Section: Team Building and Structurementioning
confidence: 99%
“…In another group, Gallup defines strengths as talents, or a combination of skills, knowledge and abilities (Clifton & Harter, 2003). While these strengths definitions differ and have both been criticized (Moore, van Mierlo, et al, 2021), overall, researchers tend to agree that strengths are innate to a certain degree (Steger et al, 2007), can be influenced by the social environment (Moore, Bakker, et al, 2021) and can be developed when actively identified and used (van Woerkom et al, 2020). While talents may not necessarily be energizing to the user (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using personal strengths can allow individuals to feel a valued part of the group, while still maintaining their uniqueness, which are important antecedents of OCB (Farmer et al, 2015). When people use their strengths in a social setting, others see those capabilities and respond in a positive manner, which can increase a sense of belonging and thriving (Moore, Bakker, et al, 2021; van Woerkom et al, 2020). Indeed, one experimental study showed that when a classroom participated in a strengths intervention, students' feelings of class cohesion and relatedness increased compared to the control group (Quinlan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%